Dielectric Properties and 3D-Printing Feasibility of UV-Curable Resin/Micron Ceramic Filler Composites - Yijia Fu; Wendong Li; Man Xu; Chao Wang; Liyuan Zhang; Guanjun Zhang (Advances in Polymer Technology)
To prepare high-permittivity composite materials for dielectrically functional gradient materials (d-FGMs) by the stereolithographic 3D-printing technique, three ceramic powders (i.e., alumina, barium titanate, and strontium titanate) are selected as functional fillers for a UV-curable resin matrix. The viscosity and UV curing depth of the uncured slurry are tested for feasibility of 3D printing. Comprehensive electrical properties, including volume resistivity, permittivity, dielectric loss, and breakdown strength of the cured composites are measured. The effects of the filler types, morphologies, particle sizes, and volume fractions on the UV curing characteristics of the slurry and dielectric properties of cured composites are systematically analyzed. The experimental results show that spherical fillers with large particle sizes, smooth surfaces, and high permittivity are conducive for reducing the slurry viscosity, increasing curing depth and adjusting the composite’s permittivity over a wide range. We believe that the proposed strategy for material system establishment can improve the 3D printability of high-permittivity composites and promote other applications of the d-FGMs by the stereolithography technique.